TAHAPAN JARINGAN AKTOR DALAM PENGEMBANGAN DESA WISATA WONOLOPO KECAMATAN MIJEN KOTA SEMARANG - Nabella, Anzilna R.; Yuniningsih, Tri; Djumiarti, Titik (Journal of Public Policy and Management Review, 2024)
The development of Wonolopo Tourism Village has the aim of alleviating poverty, advancing community welfare. The development of the Wonolopo Tourism Village requires the participation of various actors. There were several stages that experienced problems related to the actor relationships within it. Shows that the actor network stages in the development of the Wonolopo Tourism Village are less than optimal. The aim of this research is to analyze the actor network stages in the development of the Wonolopo Tourism Village and analyze supporting and inhibiting factors. The method used in this research is descriptive qualitative. With data techniques through interviews, observation and documentation. The results of this research explain that there are actors who have different views. The impact of tourism village has not been felt by the entire village community. The actions by Disbudpar Kota Semarang as the main actor have not been implemented optimally by Pokdarwis Manggar Selaras. Supporting factors in developing the Wonolopo Tourism Village are the same values, regular meetings, and openness of information. Meanwhile, the inhibiting factors are the potential not being integrated with each other, differences in interests, lack of community participation, not considering the renewal of SK Walikota Nomor 556/407 Tahun 2012.